Effects of several TIG weld repairs on the axial fatigue strength of AISI 4130 aeronautical steel-welded joints - Nascimento, M. P. [UNESP]; Voorwald, Herman Jacobus Cornelis [UNESP]; Payao Filho, J. da C. (Wiley-Blackwell, 2012)
Welded joints of airframes critical to the flight-safety are commonly repair welded during its operational live. In this study, the effect of up to three weld repairs by gas tungsten arc welding (GTAW) on the axial fatigue strength of AISI4130 steel used in an airframe critical to the flight-safety was investigated. The tests were performed on hot-rolled steel plate specimens, 0.89 mm thick, with load ratio R= 0.1, constant amplitude, at 20 Hz frequency and room temperature. The results obtained indicated that the axial fatigue strength decreased with the GTAW process itself, and with the subsequent repair cycles, as a consequence of microstructural and microhardness changes and of weld profile geometry factors, which induced high stress concentration at the weld toe.
Keywords: GTAW; heat-affected zone; high strength low alloy steel; microstructure; repair welding; weld metal; weld toe notch